Investigation and research on nursing knowledge and attitude of pressure injury in nursing students (实习护生压力性损伤护理知识和态度现状调查分析) - LIU Chunfeng (刘春凤); CHEN Changrong (陈长蓉); PANG Siyu (庞思羽); HU Jing (胡静); CHEN Chunping (陈春萍); CHEN Yachun (陈亚淳); LI Ming (黎明) (中西医结合护理, 2021)
Objective To investigate the nursing knowledge and attitude of pressure injury of nursing students who were about to finish clinical practice, and to provide reference for pressure injury training in schools and clinics. Methods Totally 188 nursing students from 3 hospitals in FuLing district of ChongQing were investigated by questionnaire on nursing knowledge and attitude of pressure injury. Results The total score of nursing knowledge of pressure injury was (43. 26±16. 14) points , 158(84. 04%)cases scored less than 60 points and 30(15. 96%)cases scored 60 or more points. The score of attitude was (41. 07±4. 50) points. There was a significant difference in score of nursing knowledge between nursing students with different number of sources of nursing pressure injury knowledge (P<0. 05). There was a significant difference in score of nursing attitude to pressure injury between nursing students with or without experience of pressure injury management (P<0. 05). Conclusion Nursing students have a positive attitude towards the nursing of pressure injury, but their knowledge level of pressure injury needs to be improved. It is required to strengthen the training of nursing students to improve their knowledge level of pressure injury, so as to ensure the safety of patients. (目的 调查重庆市涪陵区即将完成实习的护生压力性损伤护理知识和态度, 为学校和医疗机构开展压力性损伤培训提供参考依据。方法 采用压力性损伤护理知识和态度问卷对重庆市涪陵区3所医院共188名实习护士进行调查。结果 实习护生压力性损伤护理知识得分(43. 26±16. 14)分, 其中<60分 158(84. 04%)例, ≥60分30(15. 96%)例; 态度问卷得分(41. 07±4. 50)分。不同护理压力性损伤知识来源途径数量的护生的压力性损伤护理知识总分比较, 差异有统计学意义(P<0. 05); 是否护理过压力性损伤患者的护生的压力性损伤护理态度总分比较, 差异有统计学意义(P<0. 05)。结论 护生对压力性损伤护理态度积极, 但压力性损伤知识水平有待提高。实习医院和学校应加强护生培训, 提高其压力性损伤知识水平, 从而保障患者安全。)